Efeitos agudos da técnica de insuflação-exsuflação mecânica sobre o pico de fluxo de tosse e volumes da parede torácica em indivíduos com Esclerose Lateral Amiotrófica - Vieira, Rayane Grayce da Silva (2023)
Introduction: Amyotrophic Lateral Sclerosis (ALS) is a multisystemic neurodegenerative disease with clinical, genetic and neuropathological heterogeneity, with cerebral impairment, characterized by reduced lung volumes and ineffective cough, its main cause of morbidity and mortality. Mechanical insufflation-exsufflation (I-EM) consists of increasing the expiratory air flow and, thus, promoting an increase in the peak cough flow (PCF) and the removal of secretions. Objective: To analyze and describe the acute effects of applying the I-EM technique on PCF and operating volumes of the chest wall (PT) in individuals with ALS. Methodology: Analytical observational study, composed of individuals with a probable or definitive diagnosis of ALS. Initially, sociodemographic and clinical data were collected, including assessment of pulmonary function (spirometry) and respiratory muscle strength (maximum respiratory pressures, MIP and MEP). Then, the PT and PCF volumes were evaluated before (Pre I-EM) during (I-EM) and after the application of the I-EM technique (Post I-EM), through Optoelectronic Plethysmography (OEP). Results: Nine individuals with ALS who were not yet using an I-EM device were evaluated. Presenting mostly ALS of spinal onset (67%), male gender (56%) and mean FVC of 70±15.7%. The I-EM technique does not cause alterations in the PCF after performing the technique. A reduction in heart rate (p<0.003) of subjects 80 bpm (73 – 94) vs. 71 bpm (67 – 76) was observed immediately after the technique. There was a strong positive association (r = 0.73, p<0.003) between the bulbar function domain of the ALSFRS-R/BR and post-MI PFT. No differences were observed in the other variables. Conclusion: The I-EM technique was not able to increase PCF, as well as influence the thoracoabdominal pattern of individuals with ALS. So far, we can only observe that impairment of bulbar function is associated with a reduction in the generation of PCF in these pati ents. Our sample size was insufficient to detect changes in the final outcome measures.